Interpretations of Al-Amanah among Muslim scholars and its role in establishing peace in society - Islam, Md Sirajul; Samsudin, Sofiah (Sage Publishing, 2018)
Al-amanah (honesty) is a fundamental virtue associated with all aspects of human actions. Its fulfillment is a command of the Almighty Allah and His Messenger. To achieve its understanding and in order to realise its significance in the contemporary world, we examine the concept of al-amanah as it is understood by experts from different disciplines. The study concentrates on the interpretations of the Qur’anic word al-amanah, mentioned in the Surah al-Ahzab 33: Ayah 72, which talks about it in various aspects of a person’s life. The study presents the meaning of al-amanah according to lexicographers and Muslim scholars from several disciplines such as tafsir, hadith, Islamic jurisprudence, as well as ethics. In conclusion, the study finds that al-amanah enables humans to eliminate ignorance, injustice, treason and so on from society, thus creating a more peaceful environment.